Keynote: Translating innovation to the Point of Care - Medical 3D printing for personalized treatment solutions (Transactions on Additive Manufacturing Meets Medicine, 2024)
Point-of-care medical 3D printing is revolutionizing healthcare by enabling the creation of personalized treatment solutions directly within clinical settings. This talk delves into the transformative potential of this technology, focusing on its application in producing patient-specific models, prosthetics and customized implants. The presentation will highlight the latest advancements in the realm of medical 3D printing and discuss the practical aspects of its integration into clinical digital workflows, including regulatory challenges, quality assurance, and material considerations. Through compelling case studies, the talk will illustrate how point-of-care medical 3D printing enhances surgical precision, reduces recovery times, and improves patient outcomes, paving the way for a new era of personalized medicine.
Keywords: Point of Care